Isolation, Docking and Cytotoxicity Evaluation Against Cholangiocarcinoma of Labdanes from Curcuma petiolata - Suthiwong, Jittra; Pitchuanchom, Siripit; Wattanawongdon, Wareeporn; Hahnvajanawong, Chariya; Yenjai, Chavi (Asian Journal of Chemistry, 2014)
Labdanes 1-4, stigmasterol (5) and vanillin (6) were isolated from the rhizomes of Curcuma petiolata. Compounds 2-4 exhibited strong to moderate cytotoxicity against cholangiocarcinoma cell lines. Compound 3 showed strong cytotoxicity with IC50 values ranging from 5-11 μg/mL. The molecular modeling was studied using the AutoDock 4 program. The docking results reveal that 3 interacted with EGFR through the 2 H-bond at Gln767 and Met769 with binding energy of -6.89 kcal/mol.